Impact of time-of-day and chronotype on neuromuscular performance in semi-professional female volleyball players - Martín-López, J.; Sedliak, M.; Valadés, D.; Muñoz, A.; Buffet-García, J.; García-Oviedo, R.; Rodríguez-Aragón, M.; Pérez-López, A.; López-Samanes, A. (Chronobiology International, 2022)
This study aimed to determine if time-of-day could influence physical volleyball performance in females and to explore the relationship between chronotype and volleyball-specific performance. Fifteen young female athletes participated in a randomized counterbalanced trial, performing a neuromuscular test battery in the morning (9:00 h) and the evening (19:00 h) that consisted of volleyball standing spike, straight leg raise, dynamic balance, vertical jump, modified agility T-test and isometric handgrip tests. Chronotype was determined by the morningness-eveningness questionnaire. Compared to the morning, an increased performance was found in the standing spike (4.5%, p = .002, ES = 0.59), straight leg raise test (dominant-limb) (6.5%, p = .012, ES = 0.40), dynamic balance (non-dominant-limb) (5.0%, p = .010, ES = 0.57) and modified T-test (2.1%, p = .049, ES = 0.45) performance in the evening; while no statistical differences were reported in vertical jump tests or isometric handgrip strength. Moreover, no associations were found between chronotype and neuromuscular performance (r = -0.368-0.435, p = .052-0.439). Time-of-day affected spike ball velocity, flexibility in the dominant-limb, dynamic balance in the non-dominant-limb and agility tests. However, no association was reported among these improvements and the chronotype. Therefore, although the chronotype may not play critical role in volleyball-specific performance, evening training/matches schedules could benefit performance in semi-professional female volleyball players.